Penerapan Aplikasi SAKTI dalam Manajemen Keuangan di Perguruan Tinggi Negeri - Susanti, Christina (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
The Ministry of Finance of the Republic of Indonesia is at the forefront of developing policies that embrace the principle of e-government, leveraging information technology to streamline financial transactions. One of the key applications in this endeavor is the Sistem Aplikasi Keuangan Level Instansi (SAKTI). This study employs a robust qualitative descriptive data analysis technique, combining field observation, interviews with financial managers as SAKTI users at Poltekpar Bali, and comprehensive literature studies. This multifaceted approach ensures a thorough understanding of the SAKTI application's implementation and effectiveness in financial management. The results of this study show that financial managers at Poltekpar Bali have implemented the SAKTI application well according to laws and regulations. The SAKTI application can create cost efficiency, work effectiveness, transparency, and accountability in agency financial management. The Web-based SAKTI application can be accessed anytime and anywhere. It has an excellent security system with the support of a one-time password system. With the development of increasingly sophisticated technology, it is expected to be a challenge and motivation to develop SAKTI. The quality and competence of human resources in operating SAKTI are also critical and necessary in achieving the successful implementation of SAKTI, so training and socialization related to SAKTI are needed for all work units.